- Sanksi Pidana Dalam Tindak Pidana Kekerasan Terhadap Anak Yang Dilakukan Oleh Ibu Kandungnya (Putusan Nomor 155/Pid.Sus/2020/Pn Kpg): - - Karina Putri Marina; Vience Ratna Multiwijaya (Faculty of Law, Universitas Trisakti, 2023)
Children are something that cannot be separated from the continuity of human life. Child protection law classifies children in conflict with the law as children in conflict with the law or children as subjects (perpetrators), children as objects (victims), and criminal sanctions. The judge's considerations should be used as a guide to see whether the imposition of criminal sanctions contained in the decision is final or not, by linking it to the article that is used as the basis for imposing criminal sanctions. Some of the problems that arise are whether the perpetrator's actions were appropriate or not by Article 80 paragraph (1) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection (Decision Number 155/Pid.Sus/2020 /PN Kpg) and how to punish perpetrators of criminal acts of violence against children committed by their biological mothers (Decision Number 155/Pid.Sus/2020/PN Kpg). This action is inappropriate based on